THE EFFECT OF ANIONIC OIL ON THE SOFTENING PROCESS OF OLD STOCK UPHOLSTERY LEATHER USING PADDING METHOD - Fadzkurisma Robbika; Nais Pinta Adetya; Sofwan Siddiq Abdullah; Atiqa Rahmawati; Heru Budi Susanto (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Location and mechanism of leather storage that is not ideal can cause changes in the character of the old stock leather. One of the effects that is often found when storing finished leather is reducing skin softness. The conventional method of increasing leather softness of old stock is through a mechanical staking process. Staking will only be effective in softening the leather if the leather has enough oil content, if it doesn't have enough oil content it will potentially cause cracks in the grain. In this study, control leather (K) was only given mechanical treatment. Meanwhile, for treatment leather (T), the mechanical process is carried out before and after adding mayonnaise oil using a rubbing method on the flesh to maximize the oil lubrication effect on old stock leather. The use of anionic oil, mayonnaise oil, which is applied to the flesh of the skin using the wiping method on T skin, produces a higher difference in the increase in softness, namely 0.5 mm, when compared to K leather which only undergoes a mechanical process (staking and toggling), namely 0.3 mm. This shows that the addition of mayonnaise oil and emulsifier to the flesh is able to re-lubricate the leather fibers thereby increasing skin laxity.